Genome of Lumpy Skin Disease Virus - Tulman, E. R. (American Society for Microbiology, 2001)
Lumpy skin disease virus (LSDV), a member of the capripoxvirus genus of the Poxviridae, is the etiologic agent of an important disease of cattle in Africa. Here we report the genomic sequence of LSDV. The 151-kbp LSDV genome consists of a central coding region bounded by identical 2.4 kbp-inverted terminal repeats and contains 156 putative genes. Comparison of LSDV with chordopoxviruses of other genera reveals 146 conserved genes which encode proteins involved in transcription and mRNA biogenesis, nucleotide metabolism, DNA replication, protein processing, virion structure and assembly, and viral virulence and host range. In the central genomic region, LSDV genes share a high degree of colinearity and amino acid identity (average of 65%) with genes of other known mammalian poxviruses, particularly suipoxvirus, yatapoxvirus, and leporipoxviruses. In the terminal regions, colinearity is disrupted and poxvirus homologues are either absent or share a lower percentage of amino acid identity (average of 43%). Most of these differences involve genes and gene families with likely functions involving viral virulence and host range. Although LSDV resembles leporipoxviruses in gene content and organization, it also contains homologues of interleukin-10 (IL-10), IL-1 binding proteins, G protein-coupled CC chemokine receptor, and epidermal growth factor-like protein which are found in other poxvirus genera. These data show that although LSDV is closely related to other members of the Chordopoxvirinae, it contains a unique complement of genes responsible for viral host range and virulence.